International Borrowing : Negotiation and Renegotiation - Bradlow, Daniel D.; Jourdin, Willis W.; International Law Institute (Washington, D.C.) ([Washington, D.C.] : International Law Institute, 1984)
These volumes constitute a comprehensive text on inter-national borrowing. They contain the writings of practitioners and academics, case studies, historical data and examples of many of the basic documents in international finance
Vol.1
Includes bibliographies.
osc 13/6/17
Loans
Keywords: Debts, External; Debt relief; Loans, Foreign